Association between Psychological Conditions and Obesity in Elderly - Rattanabun, Warongporn; Sittiprapaporn, Phakkharawat; Pengsuwankasem, Nuttapon; Sangmanee, Nipapan; Rintra, Jarasphol (Greater Mekong Subregion Medical Journal, 2024)
Background: Obesity has been related to psychological disorders such as depression and has been shown to be a key contributor to morbidity and to adversely affect working ability and quality of life. Objective: The purpose of this study was to explore the association between body mass index (BMI) and depression amongst elderly people. Materials and Method: This was a cross-sectional analytic study. Participants were living in Suphan Buri Province, Thailand. Data, including demographic information, body composition record, The Thai geriatric depression scale: TGDS-15 assessment was used to measure levels of depression from 34 elderly people. Obesity and normal weight were defined as body mass index ≥ 25 and 18.5-22.9 kg/m2, respectively. Results: The association between depression and obesity were explored, controlling for age and BMI. After adjustments, a higher level of depression was found in obese elderly (compared with normal weight elderly) but not statistically significant between group. However, no significant association between depression and BMI. The positive associations between depression with BMI, weight, and the percentage of body fat, after controlling for potential confounders. Conclusion: The present study found a positive association between depression in this obese elderly group. Future research should continue to explore the complex nature of obesity and develop more appropriate assessments and interventions to confirm these findings.